Study of the rams’ jumping order - Oláh, János; Vass, Nóra; Kusza, Szilvia; Posta, János; Pécsi, Anna; Radácsi, Andrea; Harcsa, Attila; Gyimóthy, Gergely; Kovács, András; Jávor, András (Acta Agraria Debreceniensis, 2010)
The bevahiour of Babolna Tetra, Ile de France and Suffolk rams was studied at semen collection by artificial vagina. The sequence of rams coming out of the group to the place of semen collection and the number of jumpings needed to ejaculation were observed. It was investigated if there were changes in these characters at different occasions, and did they show connection to the body condition. The number of jumpings before ejaculation was different in the different breeds. Semen was taken at the first jump from 63% of the Suffolk, 56% of the Babolna Tetra and 55% of the Ile de France rams. There was no early ejaculation at the Ile de France, but it was common among the Suffolk rams. The greatest changes in the jumping order between different semen collections were observed in the Babolna Tetra breed. There was a medium correlation in the Suffolk breed between the jumping order and body condition in the autumn and spring, which was tight and significant in winter.